Framing Analysis of the Shooting of 6 Laskar FPI on Online Media Detik.com and Tribunnews.com. - Ketut Wiriyanto; Umaimah Wahid (2022)
This article examines the News Outlining Examination of the shooting of 6 FPI troops in Web-based Media detik.com and tribunnews.com 7 and 13 December 2020 versions. This exploration utilizes a valuable worldview and media portrayal utilizing the Zhong Dan Dish and Gerald M. Kosicki. Detik.com and tribunnews.com are public web-based media, which are a lot of popular by Indonesians. From the aftereffects of this study, it was found that report from the two internet based media had different outlining or perspectives, especially the pros and cons of the police.